DEVELOPMENT OF STUDENTS' COMPETENCE IN WORKING WITH INFORMATION IN PHYSICS LESSONS (World Bulletin of Social Sciences, 2023)
In this article, information is reflected on the issues of developing students' competence in working with information in physics classes, performing laboratory exercises using various software tools, multimedia devices.